Optimization of lychee wine fermentation process using response surface methodology to reduce acetic acid content - Rina, Wu; Ping, Zhu; Yuhui, Shang; Qiuping, Zhong (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Acetic acid is the main component of the volatile acid in the wine. However, excessive amounts of acetic acid negatively affect wine quality. The study aimed to decrease acetic acid content produced by Saccharomyces cerevisiae fermentation after adding metal ion at different temperatures. Response surface methodology (RSM) was used to predict the optimum conditions for acetic acid removal. A central composite design was employed for the experiments and results were analyzed to obtain the best possible combination of fermentation temperature (X1: 16°C-24°C) and concentrations of potassium (X2: 0-12.0 mM), magnesium (X3: 0-8.0 mM), and calcium ions (X4: 0-0.2 mM) that would generate the minimum acetic acid in lychee wine at an initial acetic acid concentration of 1.5 g/L. Experimental data were fitted to a second-order polynomial equation using multiple regression analysis and analyzed using analysis of variance (ANOVA). During fermentation under pre-established conditions, the correlation coefficients R2 and Adj-R2 of the models for acetic acid removal were 0.9487 and 0.9007, respectively. After testing, the optimum conditions for acetic acid removal were determined as follows: fermentation temperature of 20°C; potassium, magnesium, and calcium ion concentrations of 10.1 mM, 6.1 mM, and 0.2 mM, respectively. The experimental acetic acid content of lychee wine under optimal conditions was found to be 0.309 g/L, which agreed well with the model-predicted value of 0.314 g/L. Keywords: lychee wine, acetic acid, fermentation, Saccharomyces cerevisiae, metal ion, response surface methodology DOI: 10.3965/j.ijabe.20160906.2270 Citation: Wu R N, Zhu P, Shang Y H, Zhong Q P. Optimization of lychee wine fermentation process using response surface methodology to reduce acetic acid content. Int J Agric & Biol Eng, 2016; 9(6): 223-230.